Solid focal liver lesion characterisation with apparent diffusion coefficient ratios. Issue 1 (1st July 2013) - Sutherland, Tom; Steele, Emma; van, Frans; Yap, Kelvin
Abstract Introduction Non‐invasive characterisation of focal liver lesions using diffusion‐weighted imaging (DWI) has been heavily investigated and has shown substantial overlap between benign and malignant lesions. We have calculated a ratio of lesion to normal liver to determine if it improves accuracy for correct categorisation. Method All hepatic MRI studies performed between 1st April 2009 and 26th September 2011 were retrospectively reviewed. Patients with solid focal liver lesions in whom a diagnosis could be established and had lesions over 10 mm were included. Haemangiomas, cysts and patients with chronic liver disease were excluded. Apparent diffusion coefficient (ADC) values were calculated for each lesion and adjacent normal liver on breath hold DWI. Results Two hundred fifty‐eight studies were performed and 206 were excluded leaving 52 scans and 58 lesions of which 47 were benign and 11 were malignant. The mean ADC value for benign lesions was 1196.6 (two standard deviations (2SD) = ±399.9) and of benign liver 1101.5 (2SD = ±329.8) with a ratio of benign lesion to benign liver of 1.1005 (2SD = ±0.3783). The mean ADC of malignant lesions was 1153.0 (2SD = ±604.9) and malignant liver of 1080.7 (2SD = ±533.4) giving a malignant lesion to malignant liver ratio of 1.0890 (2SD = ±0.4975). None of these results were statistically significant (all P > 0.5). Conclusion DWI is unable to reliably differentiate solid benign lesions from solid malignant lesions.